Monitoring System Application for Evaluating the Performance of Lecturers and Credit Score Assessment Team for Proposing Lecturers' Functional Positions - Reza Yus Putra; Murniati Murniati; Bahrun Bahrun (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study is to analyze the use of the monitoring system application for evaluating the performance of lecturers and the role of the credit score assessment team in improving the quality of services for proposing lecturers' functional positions. This research uses quantitative research with descriptive methods. This research was conducted at the Regional XIII Higher Education Service Institute. The sample consists of lecturers who have proposed a functional promotion through simonekid. The total number of subjects is 121 people. The data collection technique used a questionnaire with a Likert scale. The data analysis used descriptive statistical analysis. The result of the research is that the use of the information system application monitoring and evaluation of lecturer performance (simonekid) gets a very satisfactory number, which is more dominant, namely 42% of the total respondents. The use of the information system application for monitoring and evaluating lecturer performance (simonekid) greatly facilitates the performance of the Credit Score Assessment Team. The conclusion is that the use of an information system application for monitoring and evaluating lecturer performance (simonekid) and the role of the credit score assessment team has helped improve the quality of service for proposing the Functional Position of Lecturer in private universities at the Higher Education Service Institution Region XIII Aceh.